Docking and Dynamics Studies: Identifying the Binding Ability of Quercetin Analogs to the ADP-Ribose Phosphatase of SARS CoV-2 - Arfan, Arfan; Muliadi, Rahmat; Malina, Rachma; Trinovitasari, Nita; Asnawi, Aiyi (Department of Chemistry, Faculty of Sciences and Informatics, University of Jenderal Achmad Yani, 2022)
The SARS-CoV-2 coronavirus outbreak has resulted in severe pneumonia, even death (COVID-19). ADP-Ribose phosphatase (ADPR), a highly conserved macrodomain of this virus, was appropriate for viral RNA replication and transcription. According to studies, quercetin suppresses the main protease and 3-chymotrypsin and papain-like proteases, exhibiting antiviral efficacy against SARS CoV-2. However, quercetin analogs to ADPR have yet to be investigated. This study aims to obtain candidate compounds for ADPR based on binding energy, interaction mode, and binding stability using docking and molecular dynamics (MD) studies.The native ligand (AMP) has estimated binding energy based on docking results of -7.35 kcal/mol. Quercetin analogs, lig_C00013871 (Quercetin 3-(2''-galoylrutinoside), lig_C00006532 ([5',5']-Bisdihydroquercetin), and lig_C00013874 (Quercetin 3-(2G-(E)-p-coumaroylrutinoside) has more negative binding energy, with estimates of -9.43, -9.26, and -8.98 kcal/mol, respectively. These results align with binding energy estimates based on MM-GBSA of -14.76, -29.39, -34.90, and -42.79 kcal/mol for AMP, lig_C00006532, lig_C00013871, and lig_C00013874, respectively. According to the MD simulation, lig_C00006532 and lig_C00013874 will be more effective in stabilizing the ADPR complex. Finally, these two analogs are potential candidate compounds as ADPR inhibitors of SARS CoV-2.